AVULSION OF DECIDUOUS TEETH: CONTRAINDICATIONS AND IMPACT ON THE DEVELOPMENT OF PERMANENT TEETH - Meira Soares, Mariana; Caroline Ribeiro Lacerda, Anne; de Almeida Rodrigues, Amanda; Jessica Dos Santos Nascimento, Ana; Luzia Coelho Bezerra de Carvalho, Isabela; Gama de Oliveira Muniz, Letícia; Jordania Lino Figueredo, Lívia; Carvalho Rodrigues, Jamilly; Cesár Ferreira Gomes, Júlio; de Souza Pereira, Malvina (Health and Society, 2025)
Introduction: Dental avulsion is defined as the complete displacement of the tooth out of the alveolus, resulting in rupture of the periodontal ligament and, in some cases, fractures of the alveolar bone. Reimplantation of avulsed deciduous teeth is widely contraindicated. This is because this process can generate additional trauma to the permanent successor, especially due to the possibility of intrusion or direct injury to the germ. Objective: To analyze the clinical implications and contraindications of the reinsertion of avulsed deciduous teeth, highlighting the risks of complications for the permanent successor teeth and the impact on child dental development. Methodology: To develop this integrative literature review, the Pubmed, Scielo and BVS databases were used. Articles published between 2014 and 2024, covering the Portuguese, Spanish and English languages, were selected. Results: After a thorough review, the final set of studies included a total of 16 articles, indicating that the replacement of deciduous teeth is directly associated with several complications in those that will erupt later. Among the main consequences, damage to the permanent tooth germ stands out, resulting in changes in its growth, color and root curvature. Although there are few studies on the subject, it is clear that these factors can cause misalignment and delay in the eruption of permanent teeth, emphasizing the contraindication of reinsertion of the element. Conclusion: Tooth avulsion affects not only oral health, but also the aesthetics and quality of life of these patients. In these cases, the role of the dentist is essential, both to safely replant the tooth and to guide parents and guardians on the necessary care. Trauma to deciduous teeth can have a direct impact on the growth of permanent teeth, and specialized care, combined with prevention, helps to reduce the risk of sequelae that can affect the child throughout life.